Kepemimpinan H. Ismail dalam Menggerakkan Perlawanan Rakyat Kerinci Menentang Imperialisme Belanda Tahun 1903 - Rio Mastri; Etmi Hardi; Hendra Naldi (Galanggang Sejarah, 2019)
This study reviews “The Leadership of H. Ismail in Moving Kerinci People Opposition Against Netherlands Imperialsm in 1903”. This research is motivated by the great role of H. Ismail, but He was not well known by the public. His existence was not well known by the public as good as Mat Kasib namely Depati Parbo known by the public. This research was conducted using historical method that consist of 4 stages. These results indicate that a major role of H. Ismail that he couldn't underestimate in ‘Perang Tahun Tigo’ period. In addition, this study also showed that H. Ismail is the only figure who can consolidate the troops of the many regions in Kerinci. When the first period of his leadership, he only led the people who came from his region. He got a victory after defeated the enemy successfully. Entering the second period, after the war ended, the Kerinci people from another regions chose the join with him. Unfortunately in this period they accepted their defeat And had to go back a way to the forest. H. Ismail there is still a role as a leader in the guerrilla war, he still be a leader until he was old, the people especially his family persuaded him to "down the mountain" and live as an ordinary people.